A study on relationship between training and organizational commitment among nurses in Hospital Sultan Abdul Halim, Sungai Petani, Kedah / Haris Abu Bakar and Nur Izlila Othman - Abu Bakar, Haris; Othman, Nur Izlila (2010)
The purpose of this study is to gain a better understanding of the relationships between training and organizational commitment of nurses at Hospital Sultan Abdul Halim, Sungai Petani, Kedah. This study focuses on investigates the most significant effect towards frequency of training, perceived organizational support for training, and motivation to learn from training. Research was conducted through a survey instrument consisting of demographic, training, and organizational commitment questions. Participants in the research included 132 nurses who worked at Kenanga’s Ward in the Hospital Sultan Abdul Halim, Sungai Petani, Kedah. Responses from the survey were statistically analyzed with cronbach’s alpha, descriptive statistics, pearson correlation, and multiple regression analysis. Further, results of the study indicate to have a significant relationship to organizational commitment. The findings of this study can be use to improve organizational effectiveness and provide guidelines for future researchers to do research based on this particular topic.